Perceptions of student nurses of their career progression opportunities - Nkhoma, Catherine (My University, 2022)
Aim: This research aims at exploring the perceptions of student nurses towards their career progression opportunities that are available to them. The probability of a student pursuing and remaining in the nursing profession is influenced by the student's view of the profession. Background: This study is all about how the student nurses perceive their opportunities as they progress in their career. In this report, the researcher looked at the perception of the nursing career by undergraduate students. The findings from this research will help to understand the perceptions that student nurses have about their career, career plans and their understanding of progression once they have completed their training. Once this is known, it would help nursing educators on how to prepare for working life realities of nurses, thereby minimising the connection between this and the students’ expectations. Methodology: Semi-structured interviews were used for gathering data in this study as part of a qualitative research approach. Thirteen (n = 13) participants from the study population, (N = 90) nursing students at a university in Gauteng, South Africa, were invited to take part in the study. All thirteen interviews were conducted upon which theoretical data saturation was reached at interview number ten. Due to the Covid-19 restrictions and students being taught remotely interviews were conducted using an electronic meeting platform familiar with the students namely ZOOM. The interviews were transcribed verbatim and analysis was done using thematic analysis approach. Findings: Three themes were generated and were categorised as: (i) Careers opportunities after graduation, (ii) Support for career progression and (iii) Barriers to career progression. Conclusion: The study’s major goal was to find out student nurses’ perceptions when it comes to career progression. The study used a qualitative research method and managed to achieve this goal. Participants mentioned what career progression is all about, they highlighted the career opportunities available to them, what they consider to be barriers to career progression as well as what they thought is the support they would need to promote career progression.
A research report submitted in fulfilment of the requirements for the degree of Master of Nursing to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2022